Characterization of platelet-specific mRNA by real-time PCR after laser-assisted microdissection - Fink, Ludger; Hölschermann, Hans; Kwapiszewska, Grazyna; Prakash Muyal, Jai; Lengemann, Björn; Bohle, Rainer Maria; Santoso, Sentot (Thrombosis and Haemostasis, 2003)
Circulating anucleate platelets contain minute amounts of residual megakaryocytic-derived mRNA. To study cell type-specific gene expression in platelets, an accurate and sensitive method to detect and quantify platelet mRNA that excludes contamination with leukocyte RNA is mandatory. Applying laser-assisted microdissection and manipulation (LMM) we could isolate platelets from hemalaun-stained cytospins under permanent visual control and after laser-photolysis of nucleated blood cells. For mRNA quantification, the platelet-specific mRNAs were subsequently measured by real time RT-PCR. High-copy β3 integrin and low-copy α2 integrin as well as tissue factor (TF) transcripts were analyzed in LMM-harvested platelets. In 91.2% (83/91) β3 integrin was detectable with a mean threshold cycle (CT) value of 32.5 ± 3.2 (≤ 50,000 cells). The low-copy α2 integrin mRNA was positive in 84.4% (38/45) with CT mean value of 36.9 ± 1.3, indicating that the relative expression of α2 integrin mRNA in platelets was about 130 times lower than β3.The TF transcript was undetectable in all samples. Comparing platelet mRNA from LMM isolation to that from limiting dilution series resulted in a high accordance for β3 integrin transcript in both, recovery (91.2% vs. 95.2%) and CT value (32.5 vs.32.8).These results demonstrate that the combination of LMM and real-time RT-PCR is a valuable tool for precise, platelet-specific mRNA analysis without contamination of other cells.
Keywords: Platelet; laser-microdissection; real-time PCR; integrin; tissue factor